Larangan Membunuh Anak Karena Takut Miskin: (Kajian Tafsir Muqaran Pada Q.S Al-An’am Ayat 151 Dan Q.S Al-Isra 31) - Aziz, Muhammad Fadhlan; Yunizar, Muhammad; Pebrianti, Suci; Iryanti, Rida Maryani; Jamaruddin, Ade (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2023)
This research starts from a case of the crime of murder by parents of their children because they were afraid of poverty. This action was similar to the actions of the Jahiliyyah community at that time. In response to this, Allah SWT revealed verses, namely Q.S Al-An'am verse 151 and Q.S Al-Isra verse 31. These two verses editorially have similarities and similarities. Even though they are similar, it is very possible that there are differences in meaning in these two verses. Therefore, this research has the aim of analyzing the similarities and differences of the two verses as well as presenting a comparison of the opinions of the ulama on these two verses. The method used in this research is analytical descriptive and the data used in this research is qualitative data sourced from primary and secondary data using library study data collection techniques. The results of this research can be concluded that Q.S Al-An'am verse 151 and Q.S Al-Isra verse 31 both have something in common, namely the prohibition on killing children. The difference between these two verses lies in the addition of the word "khasyah" which gives rise to a different meaning in each verse.